(untitled) (Research, Society and Development, 2020)
The present study aimed to evaluate the content of bioactive compounds in moringa seed flour, with an initial humidity of 50% or 70%, after the solid state fermentation process using Aspergillus niger. Extracts of fermented and unfermented moringa seed flour were obtained using distilled water, 40% and 80% ethanol, 40% and 80% acetone and the contents of phenolic compounds and total flavonoids were determined. Antioxidant (by DPPH, ABTS and FRAP) and antimicrobial activities were determined for extracts with greater increases in phenolic compounds and total flavonoids after fermentation. The phenolic compounds were quantified by high performance liquid chromatography. The greatest increase in phenolics (395.4%) in relation to unfermented flour was obtained in extract A40% (IU = 70%) fermented for 168 hours and the highest in total flavonoids (273.7%) was in the extract in E80% (UI = 50%) fermented for 168 hours. The extracts in A80% of the unfermented flour and the fermented flour (IU = 70%) for 72 hours showed greater AA by the DPPH method. The fermented extracts showed an inhibitory potential against the bacteria B. subtilis, S. aureus and S. marcescens, while no bacteria were sensitive to non-fermented extracts. Fermented extracts demonstrated higher concentrations of the compounds epicatechin, epicatechin gallate, ethyl gallate and epigallocatechin and the presence of undetected epigallocatechin gallate in the extracts of unfermented. The FES associated with extraction with organic solvents demonstrated efficiency in obtaining extracts from the flour of moringa seeds with improved bioactive potential.